Four direct measurements of the fine-structure constant 13 billion years ago - Wilczynska, Michael R. (Sci Adv, 2020)
Observations of the redshift z = 7.085 quasar J1120+0641 are used to search for variations of the fine structure constant, α, over the redshift range 5:5 to 7:1. Observations at z = 7:1 probe the physics of the universe at only 0.8 billion years old. These are the most distant direct measurements of α to date and the first measurements using a near-IR spectrograph. A new AI analysis method is employed. Four measurements from the x-shooter spectrograph on the Very Large Telescope (VLT) constrain changes in a relative to the terrestrial value (α(0)). The weighted mean electromagnetic force in this location in the universe deviates from the terrestrial value by Δα/α = (α(z) − α(0))/α(0) = (−2:18 ± 7:27) × 10(−5), consistent with no temporal change. Combining these measurements with existing data, we find a spatial variation is preferred over a no-variation model at the 3:9σ level.